Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.compbiomed.2020.103980
|View full text |Cite
|
Sign up to set email alerts
|

Toward automated severe pharyngitis detection with smartphone camera using deep learning networks

Abstract: Purpose Severe pharyngitis is frequently associated with inflammations caused by streptococcal pharyngitis, which can cause immune-mediated and post-infectious complications. The recent global pandemic of coronavirus disease (COVID-19) encourages the use of telemedicine for patients with respiratory symptoms. This study, therefore, purposes automated detection of severe pharyngitis using a deep learning framework with self-taken throat images. Methods A dataset composed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
4

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 43 publications
(47 reference statements)
0
12
4
Order By: Relevance
“…However, the AUC score of 0.975 in our study is slightly lower than the AUC score of 0.992 achieved by Yoo et al [ 13 ]. We also note that Yoo et al [ 13 ] and Askarian et al [ 14 ] did not deploy their models on a web or mobile application for clinical use.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…However, the AUC score of 0.975 in our study is slightly lower than the AUC score of 0.992 achieved by Yoo et al [ 13 ]. We also note that Yoo et al [ 13 ] and Askarian et al [ 14 ] did not deploy their models on a web or mobile application for clinical use.…”
Section: Discussioncontrasting
confidence: 96%
“…The precision in this study was very high (1.00) and the recall was high (0.89). The two previous studies by Yoo et al [ 13 ] and Askarian et al [ 14 ] did not examine precision and recall; thus, we were not able to compare our models’ performance on these metrics with that of previous work. In our study where the precision was very high, at 1.00, the implication is that the model classified all non-pharyngitis patients correctly, thus avoiding the unnecessary use of antibiotics in patients who do not require them.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, ambiguous images were eliminated by experts. While collecting the data set used in the study, images up to April 2020 were collected [9,10]. The related data set contains 131 images of the oropharynx with tonsillopharyngitis and 208 images of the normal oropharynx.…”
Section: Data Setmentioning
confidence: 99%
“…The accuracy value obtained by using 4-fold cross-validation in the ResNet50 model was 95.3%. The researchers stated that the proposed system could be used in smartphone-based applications [9].…”
Section: Introductionmentioning
confidence: 99%
“…Burlina et al demonstrated the feasibility of using low-shot learning based on automated data augmentation to classify fundus photographs with rare conditions [ 18 ]. Several researchers have utilized generative models to enlarge training datasets in order to improve the detection accuracy of diseases using very small datasets [ 19 , 20 ]. Few-shot learning based on data augmentation has also been used to detect pathological chest images of patients with COVID-19 [ 21 ].…”
Section: Introductionmentioning
confidence: 99%